Optimization of Enzyme-Assisted Extraction of Flavonoids from Corn Husks (2019)
Corn husks are an important byproduct of the corn processing industry. Although they are a rich source of bioactive compounds, especially flavonoids, corn husks are usually disposed of or used as animal feed. In this paper, we investigate their recovery by an enzyme-assisted extraction process consisting of a pretreatment of the plant material with cellulase followed by solvent extraction with aqueous ethanol. A four-factor, three-level Box–Behnken design combined with the response surface methodology was used to optimize the enzyme dosage (0.3–0.5 g/100 g), incubation time (1.5–2.5 h), liquid-to-solid ratio (30–40 mL g^(-1) ) and ethanol concentration in the solvent (60–80% v/v). Under the optimal conditions, about 1.3 g of total flavonoids per 100 g of dry waste were recovered. A statistical analysis of the results was performed to provide a quantitative estimation of the influence of the four factors, alone or in combination, on the extraction yields. Overall, the results from this study indicate that corn husks are a valuable source of flavonoids and that they can be easily recovered by a sustainable and environmentally friendly extraction process.